30 Preparing our future Doctors – use of life-cast simulated verification of death in final year medical students. (14th March 2023) - Craig, Joshua; Scott, Jessica; Moss, Nicholas; Yates, Chris
Abstract : Background: High fidelity simulation has a well-established role within undergraduate education, teaching both clinical and non-clinical factors in the management of acutely unwell patients. Verification of death is equally part of a junior doctor's role as initial management of the unwell patient; however, the verification process is often taught theoretically, focusing on the logistical and legal aspects with very little emotional investment. This, in our experiences, has led to a lack of emotional preparedness in medical undergraduates, which can lead to fear and anxiety when confronted with such situations as a newly qualified foundation doctor. Studies looking into cadaveric dissection clearly demonstrate student fear and anxiety when considering concepts such as death 1, with potential for detriment for wellbeing. Methods: Our study involved creating an educational session using a highly realistic life cast simulation model named Vivienne. Medical students took part in an interactive simulation performing death verification in real time, with simulated nursing staff and relatives to bring out the human and emotive side of this process. Our aims with the project were to improve the student's confidence in their ability to practically manage this common scenario as foundation doctors and to encourage discussion and around the non-clinical emotional aspects of such experiences to allay anxiety. Results: Using pre and post simulation questionnaires we were able to demonstrate improvement in student emotional preparedness towards the verification of death process. Compared to the pre-simulation responses there was a globally positive trend in mean scores throughout. Free text responses reflected on an overall positive experience in both practical and emotional aspects of the case. Conclusions: Due to the positive experiences thus far we have plans to expand the use of life cast simulation for training in undergraduate end-of-life care education including in discussions around resuscitation and performance of basic life support. Reference: N. Leboulanger. First cadaver dissection: Stress, preparation, and emotional experience, European Annals of Otorhinolaryngology, Head and Neck Diseases, 2011;128 (4):175–183